ADMINISTRATIVE LAW IMPLICATIONS FOR PLANTATION COMPANIES IN THE CASE OF PALM OIL THEFT - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study discusses the implications of administrative law for plantation companies in dealing with cases of palm oil theft. The main focus is on how applicable administrative regulations can help companies protect their plantation assets and prevent legal losses. Administrative law requires companies to meet legal standards, such as possession of valid business licences and the implementation of clear rule-based management systems. Additionally, companies are required to strengthen asset monitoring and maintain good relations with the local community to minimise the potential for violations, including theft. The analysis reveals that non-compliance with administrative obligations can weaken a company's legal position, particularly in theft prosecution proceedings. Conversely, companies that consistently meet legal and administrative requirements are more resilient in facing legal cases. These findings emphasise the importance of the interconnection between administrative law and operational management in creating sustainable plantation asset protection.